I drink for a reason [compact disc, unabridged] - Cross, David, 1964- (Hachette Audio, 2009)
Stand-up comedian and actor David Cross presents a scathing and hilarious critique of 21st century pop culture. Here, nobody is safe from Cross' rip-roaring humor, including the mainstream media, scandalous celebs, and religion.